Hydrological resilience of a Canadian Rockies headwaters basin subject to changing climate, extreme weather, and forest management - Harder, Phillip; Pomeroy, John W.; Westbrook, Cherie J. (Hydrological processes, 2015)
Marmot Creek Research Basin in the Canadian Rockies has been the site of intensive streamflow, groundwater, snow accumulation, precipitation, and air temperature observations at multiple elevations. The basin was instrumented in 1962, subjected to forestry experiments in the mid‐1970s, and experienced extreme flooding in 2013. Climate change, forest cover change, and recent extreme weather make the basin an ideal laboratory for studying hydrological resilience. Observations show increases in low elevation air temperature, multiple day and spring precipitation, interannual variability of precipitation, and high elevation groundwater levels. Observations also show decreases in peak seasonal snow accumulation and low elevation groundwater levels. Despite these substantial hydrometeorological and groundwater changes, streamflow volume, timing of peak, and magnitude of the peak are not changing. Streamflow volumes are also insensitive to forest cover changes and teleconnections. The June 2013 flood was unprecedented in the period of record, and the basin significantly moderated the hydrological response to the extreme precipitation; the 2013 storm precipitation depth was 65% greater than the next highest storm total over 51 years; however, the 2013 peak streamflow was only 32% greater than the next highest peak flow recorded. The hydrology of Marmot Creek Research Basin displays remarkable resilience to changing climate, extreme weather, and forest cover change. Copyright © 2015 John Wiley & Sons, Ltd.